Pengaruh Dukungan Tempat Kerja Terhadap Kepuasan Kerja pada Pegawai (Studi Kasus STMIK Duta Bangsa Surakarta) - Indra Hastuti (LPPM Universitas Duta Bangsa Surakarta, 2015)
The purpose of this study was to analyze the influence of workplace support proxy variable institutional support, instrumental support supervisor, emotional support supervisor, on job satisfaction on employee STMIK Duta Bangsa Surakarta, and analyze the influence of the role of instrumental support and emotional support coworker coworkers on job satisfaction the employee STMIK Duta Bangsa Surakarta. This research was conducted in STMIK Duta Bangsa Surakarta population in this study were all employees STMIK Duta Bangsa Surakarta number of 65 respondents. The sample in this study were 65 respondents. The sampling technique using saturated sample. Methods of data analysis using Multiple Linear Regression Analysis.The analysis showed Institutional support, instrumental support Tops, Tops Emotional support, instrumental support Colleagues, Partners Emotional support positive and significant effect on work satisfaction. From this study has implications that to improve employee satisfaction College of advised institutions provide employees who are able to meet the needs of customer service, Institutions providing adequate equipment to perform the work according to his duties, the institution always provide good support for employees, every case of problems with employees associated with the agency resolved in a more either because it is proven to increase job satisfaction.